Pengaruh Kapabilitas Aparat Pengawasan Intern Pemerintah Terhadap Kinerja Pengelolaan Keuangan Pemerintah Kabupaten dan Kota di Provinsi Papua Barat - Irda Nurhamsyah; Meinarni Asnawi; Paulus K. Allo Layuk (Universitas Cenderawasih, 2022)
This study aims to examine and analyze the influence of the capability of the government's internal supervisory apparatus to the level of its constituent elements based on the Internal Audit Capability Model (IACM) on the performance of regional financial management. The population of this study is 135 internal audit practitioners consisting of functional auditors and PPUPD officials at the Regency and City Inspectorate in West Papua Province. The research sample was 103 functional auditors and PPUPD officials at the Regency and City Inspectorates in West Papua Province. The study used primary data through the distribution of questionnaires. The analytical method used is multiple linear regression. The results showed that the APIP Human Resource Management variable partially had a positive and significant effect on the performance of regional financial management. The variables of APIP Roles and Services, APIP Professional Practices, APIP Accountability and Performance Management, Organizational Culture and Relations and Governance Structure partially have a positive but not significant effect on regional financial management performance. The six variables simultaneously have a positive and significant effect on the performance of regional financial management.